Estudo da atividade pozolânica de micropartículas de vidro soda-cal, incolor e âmbar, e sua influência no desempenho de compóstos de cimento Portland - Fernando Augusto Sales (2014)
Portland cement concrete is the most widely used building construction material worldwide, but its use is associated with high environmental costs. The extraction of billions of tons of natural resources for its manufacture impacts strongly the environment. Furthermore, the production of Portland cement demands high energy consumption and releases large amounts of carbon dioxide into the atmosphere. The use of industrial, agricultural or construction waste as alternative materials to partially or totally replace concrete aggregates or binders for concrete has been being an interesting option to obtain eco-efficient concretes. The most used wastes are usually blast furnace slag, active silica, fly ash and construction and demolition wastes. Another alternative is the use of glass waste. Several studies have investigated the use of these wastes in Portland cement compounds, either as aggregates or as supplementary cementitious materials. From these studies, it seems that there is no consensus about the influence of color and size of glass particles on the behavior of the produced compounds. Therefore, the reaction of silica with alkali can be benefic if it occurs during hardening, or it can be deleterious if it occurs in the hardened concrete. In addition, the literature has recently reported the need to better understand the kinetics of pozzolanic reaction in regard to amorphicity and particle size. Accordingly, this paper addresses the pozzolanic activity of microparticles of soda-lime glass (colorless and amber), and its influence on the performance of Portland cement compounds. The effect of partial replacement of Portland cement by 10, 15 and 20% of glass particles of about 9.5mm was investigated on the pozzolanic activity, the mechanical strength and the durability of cementitious compounds (mortar and concrete). Results revealed that the partial replacing of cement with of soda-lime glass microspheres can contribute to the production of mortars and concretes of similar workability and mechanical performance, as well as to the production of a concrete that is durable in terms of inhibition of alkali-aggregate reaction. Nevertheless, the use of glass particles made the compound more susceptible to carbonation and abrasion. We have identified the influence of glass color, which was translated in terms of carbon content, hydration heat, curing time, electrical resistivity and heat absorption capacity.